2021
DOI: 10.1039/d1sm00701g
|View full text |Cite
|
Sign up to set email alerts
|

Extending the timescale of molecular simulations by using time–temperature superposition: rheology of ionic liquids

Abstract: Molecular dynamics simulations are used to determine the temperature dependence of dynamic and rheological properties of a model imidazolium-based ionic liquid (IL). Simulation results for the volumetric properties of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…Figure C shows that it is possible to derive the TTS shift factors of the viscoelastic moduli and local displacements from the characteristic decay time of the intermediate scattering function. In order to evaluate the generality of this result, we have revisited atomistically detailed MD simulations for an imidazolium-based ionic liquid . This ionic liquid consists of the 1-(cyclohexylmethyl)-3-methylimidazolium cation ([CyhmC 1 im] + ) and the bistriflimide anion ( [NTf 2 ] − ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Figure C shows that it is possible to derive the TTS shift factors of the viscoelastic moduli and local displacements from the characteristic decay time of the intermediate scattering function. In order to evaluate the generality of this result, we have revisited atomistically detailed MD simulations for an imidazolium-based ionic liquid . This ionic liquid consists of the 1-(cyclohexylmethyl)-3-methylimidazolium cation ([CyhmC 1 im] + ) and the bistriflimide anion ( [NTf 2 ] − ).…”
Section: Discussionsupporting
confidence: 79%
“…The detailed chemical structure and a description of the simulation procedure are given in the Supporting Information (Figure S3 and section SI2). We have previously reported that the simulated volumetric and linear viscoelastic properties of this ionic liquid are in a good agreement with experiments . In Figure C, we observe that the shift factors obtained from the master MSD curves both for the cation ([CyhmC 1 im] + ) and anion ([NTf 2 ] − ) at different temperatures are collapsed on the same line a T = a T ′ = τ r when they are plotted against the rescaled ISF decay time.…”
Section: Discussionsupporting
confidence: 74%
“…We note that the implementation of the SLLOD equation, when SAOS flows are used, is only valid when the deformation frequency is above 2 × 10 −9 s −1 in our simulations. 43,50,52 For lower frequencies where the propagation of the shear forces are slow in the material, this method is not suitable. The second regime is found at intermediate temperatures (120 ≤ T ≤ 380 K) and exhibits a rapid increase of α corresponding to the glass transition of the system.…”
Section: Model and Simulation Detailsmentioning
confidence: 99%
“…The SBR modeled in this study has a T g of 274 ± 5 K, which is higher than the reported experimental value of 227 K. 72 The higher cooling rate used in simulations compared to experiments causes this apparent disagreement between experimental and simulation glass transition temperature, and it has been reported in previous literature works for linear and cross-linked polymers, ionic liquids, and asphalt. 43,49,61,73 In addition, the transition regime is broader than that in experiments. The divergence is also seen in the density close to the T g of the simulation and below that in the glassy state.…”
Section: Model and Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation